Splenectomy for immune thrombocytopenia : our 11-year experience - Antel, Katherine (Department of Medicine, 2015)
Splenectomy has been practiced for the treatment of ITP for the past few decades. Currently it is utilised when a patient is either dependent or resistant to steroid treatment and the platelet count remains less than 30Ã—109/L. Recently new agents have been added to the armamentarium used to treat ITP, including immune-suppressants such as rituximab and the new thrombopoetin-receptor agonists. This has brought into question the role of surgery for the treatment of ITP, and the need to compare the response and complication rates of splenectomy to these newer agents. Historic studies done on splenectomy for the treatment of ITP have been performed in the setting of low HIV prevalence. There is a relative paucity of data on the response rate in HIV-associated thrombocytopenia to splenectomy and the durability of response to splenectomy is unclear in this patient population. We retrospectively analysed 73 consecutive patients who underwent splenectomy for ITP from 2001 to 2011. The primary objective was to determine the rate of complete response, this was defined as a platelet count greater than 100Ã—109/L at one year post splenectomy. Results were compared between HIV positive and HIV negative patients. The secondary objectives were: to evaluate the intra-operative and postâ€ operative complications and mortality in the HIV positive and HIV negative groups, and to investigate for associations between co-morbidities, pre-operative treatment and response to splenectomy.